An environmentally benign hydration of alkynes catalyzed by gallic acid/tannic acid in water. Issue 19 (9th September 2016) - Deng, Tao; Wang, Cheng-Zhang
Abstract : A gallic acid catalyzed hydration strategy from alkynes under mild conditions has been developed. Abstract : A gallic acid catalyzed hydration strategy from alkynes under mild conditions has been developed. The catalyst system exhibits excellent activity, thus avoiding the use of any transition metal, strong acids or other toxic reagent as cocatalysts. Recycling experiments were conducted, and this procedure can be scaled up. Other tannins such as tannic acid can also be applied in this reaction which shows the potential utilization of natural feedstocks.